Implementasi Filsafat Pendidikan Islam Dalam Pembinaan Tahfidz Dan Akhlak Di Pptq Al-Fatah Purbalingga - Mujiburrohman .; Lukmanul Hakim (CV. ITTC INDONESIA, 2025)
Although [topic/issue] has received increasing attention in prior studies, research specifically addressing [clearly stated gap] remains limited. This study aims to [explicit objective, e.g., analyze the effect of A on B, evaluate the effectiveness of X, or explore the experience of Y]. A [quantitative/qualitative/mixed-method] approach was employed using a [design: survey, case study, experiment, etc.], involving [number] participants/respondents selected through [sampling technique]. Data were collected using [instruments: questionnaire, interview, observation] and analyzed with [analytical technique: regression, SEM, thematic analysis, etc.]. The findings indicate that [objective summary of main results, e.g., a significant relationship was found between X and Y, or Z emerged as the most influential factor]. These results contribute to the theoretical development of [relevant theory or concept] and expand the understanding of [topic/context]. The study concludes that [key takeaway or insight] plays a crucial role in [context], and recommends that [stakeholders] [take specific practical action or adopt a policy]. The implications of this research include theoretical contributions to the growing literature on [topic/field] and practical recommendations for[governments, institutions, industries, etc.]. Furthermore, this study highlights opportunities for future research on [emerging or underexplored issues].